Stability -Indicating RP-HPLC Method Development and Validation for the Simultaneous Estimation of Alogliptin and Metformin in Bulk and Pharmaceutical Formulations - Ganta Susmitha; Gade Sammaiah (Asian Journal of Pharmaceutical Research and Development, 2025)
A robust and precise reverse-phase high-performance liquid chromatography (RP-HPLC) method has been developed and validated for the simultaneous quantification of Alogliptin and Metformin in combination dosage forms. The analysis was conducted using a Develosil ODS HG-5 RP C18 column (15 cm x 4.6 mm i.d; particle size 5 μm) with a mobile phase comprising acetonitrile and potassium dihydrogen phosphate buffer (0.05M, pH 3.8) in a 70:30 v/v ratio, at a flow rate of 1 ml/min, with ultraviolet detection at 258 nm. The retention times for Alogliptin and Metformin were 1.97 and 5.43 minutes, respectively. The method demonstrated linearity within the concentration range of 0-150 μg/ml for Alogliptin and 0-15 μg/ml for Metformin, with a correlation coefficient (r²) of 0.998 for both compounds. The limits of detection were determined to be 0.01 and 0.03 g/ml, while the limits of quantification were 0.15 and 0.45 g/ml for Alogliptin and Metformin, respectively. The percentage relative standard deviation (%RSD) values were below 2 for both drugs. The assay results indicated that the content of Alogliptin and Metformin was 99.689% and 100.078%, respectively. The method was validated for parameters including linearity, accuracy, precision, robustness, limit of detection (LOD), and limit of quantification (LOQ) in accordance with International Council for Harmonisation (ICH Q2 (R1)) guidelines. This developed method was successfully applied for the quantitative analysis of commercially available dosage forms.